Developing advanced polymer films based on microfluidic laminar flow. (March 2022) - Cheng, Sha; Chen, Wen; Zhang, Pengchao
Abstract: With the explosive development of many emerging fields, such as wearable devices, electronic skins, and flexible batteries, it urgently needs advanced polymer films with precisely controlled physical and chemical properties. Microfluidic technology that can be used to generate controllable laminar flow in the microchannels provides new opportunity for one-step fabricating such kind of polymer films. In this review, we summarize the development of advanced polymer films with accurately controlled thickness in micro/nanometer, and heterogeneous structures and compositions, taking advantage of the unique microfluidic laminar flow. We first briefly introduce the unique characteristics of microfluidic laminar flow, and the materials and related fabrication methods of microfluidic devices. Then, emphasis is placed on the preparation strategies of advanced polymer films based on microfluidic laminar flow. Finally, we put forward personal views on future trends of this promising technology and aim to promote the development of advanced polymer films by using the microfluidic laminar flow and potential applications in various fields. Graphical abstract: Image, graphical abstract